1999
DOI: 10.1001/archinte.159.21.2542
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Active Rheumatoid Arthritis With Leflunomide Compared With Placebo and Methotrexate

Abstract: Clinical responses following administration of leflunomide, a new therapeutic agent for the treatment of RA, were statistically superior to those with placebo and equivalent to those with methotrexate treatment. Both active treatments improved signs and symptoms of active RA, delayed disease progression as demonstrated by x-ray films, and improved function and health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
407
7
36

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 658 publications
(463 citation statements)
references
References 19 publications
13
407
7
36
Order By: Relevance
“…In fact, when reviewing results from the various leflunomide clinical trials, ACR response rates of patients receiving leflunomide monotherapy were similar, if not superior, compared with the addition of leflunomide to MTX therapy (33)(34)(35) (Table 1). Again, comparing clinical trials has its limitations, but the results are clearly consistent with this interpretation.…”
Section: Study Design Issuesmentioning
confidence: 99%
“…In fact, when reviewing results from the various leflunomide clinical trials, ACR response rates of patients receiving leflunomide monotherapy were similar, if not superior, compared with the addition of leflunomide to MTX therapy (33)(34)(35) (Table 1). Again, comparing clinical trials has its limitations, but the results are clearly consistent with this interpretation.…”
Section: Study Design Issuesmentioning
confidence: 99%
“…Newer data suggest that radiographic evidence of joint damage is apparent even in patients with very early disease (11)(12)(13)(14)(15). Therefore, it is important to consider implementation of diseasemodifying drugs at earlier stages of disease.…”
mentioning
confidence: 99%
“…Therefore, it is important to consider implementation of diseasemodifying drugs at earlier stages of disease. In addition, it has been shown that despite treatment with traditional DMARDs, patients with persistent disease continue to deteriorate radiographically and lose functional capacity (13)(14)(15). This finding is especially important considering that studies have demonstrated a direct correlation between declining functional status and increased rates of morbidity and mortality (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Leflunomide, a new DMARD, has demonstrated efficacy in the treatment of RA, both clinically and in slowing radiographic progression (14,17,18). Leflunomide is a prodrug rapidly converted into the active metabolite A77 1726, which acts predominantly by inhibiting dihydroorotate dehydrogenase, an enzyme critical for the de novo biosynthesis of pyrimidine, thus prohibiting the clonal expansion of activated T cells (19).…”
mentioning
confidence: 99%